2020
DOI: 10.1111/nyas.14300
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis, antimicrobials, immunity, and lung–gut microbiota crosstalk: current updates and emerging advances

Abstract: Increasingly, gut microbiota distortions are being implicated in the pathogenesis of several infectious and noninfectious diseases. Specifically, in the absence of an eubiotic microbiota, mice are more prone to colonization and infection by Mycobacterium tuberculosis (Mtb). In this qualitative analysis, the following were observed: (1) antimicrobials cause long-term gut microbiota perturbations; (2) Mtb causes limited and transient disturbances to the lung-gut microbiota; (3) pathogens (e.g., Helicobacter hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 82 publications
(390 reference statements)
1
46
0
Order By: Relevance
“…Hence, these opportunistic pathogens demand more attention than they have been given hitherto as the rich resistome repertoire identified in their genomes makes them reservoirs of ARGs 11,14,21,43 . Moreover, being intestinal denizens and commensals, they can easily share these ARGs with facultative and obligate pathogens of humans and animals 22,4446 . Further, their presence on plants and the environment further suggests that they can share their ARGs with food-borne and water-borne pathogens 4446 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, these opportunistic pathogens demand more attention than they have been given hitherto as the rich resistome repertoire identified in their genomes makes them reservoirs of ARGs 11,14,21,43 . Moreover, being intestinal denizens and commensals, they can easily share these ARGs with facultative and obligate pathogens of humans and animals 22,4446 . Further, their presence on plants and the environment further suggests that they can share their ARGs with food-borne and water-borne pathogens 4446 .…”
Section: Discussionmentioning
confidence: 99%
“…Coupled with plasmid-borne dissemination of ARGs is the selection and expansion of specific drug-resistant clones 11,21 , which quickly spread under antibiotic pressure to overpopulate their environments, facilitating their survival and subsequent spread to other environments 14,22,23 . In cases where such clones harbour resistance plasmids, their expansion almost always lead to the concomitant replication and intra-clonal as well as inter-clonal spread of such plasmids 4,5,7,8,24,25 Thus, as such clones are disseminated through contact, food, water, farms, hospitals, and the environment, they carry with them these resistance plasmids to colonize new hosts and environments 6,26–28 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous metagenomics studies all indicated that the repertoire of bacteria in the gut microbiota significantly differed between pulmonary tuberculosis patients and controls, suggesting biological relationships between pulmonary tuberculosis and gut microbiota [ 10 ]. However, contradictory data from these studies complicated the interpretation of these differences.…”
Section: Discussionmentioning
confidence: 99%
“…In children, microbial richness was not found to significantly differ between TB-positive children and controls, although the Simpson index was found to be significantly lower in TB-positive children [ 30 ] with five different bacterial species found to be significantly balanced between the two groups [ 30 ]. The interpretation of metagenomics studies data was limited by the inherent profounder bias of the method, lack of accurate bacterial species identification [ 10 ], and the fact that detected organisms may not be viable, thus rendering them to be of limited physiological interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation